IMPLEMENTING INFORMATION AND DOCUMENTATION MANAGEMENT OFFICIAL BY PUBLIC AGENCIES IN SURABAYA - Vience Mutiara Rumata (Pusbindiklat - LIPI, 2012)
This paper describes Challenges in implementing Information and Documentation Management Officials byPublic Agencies in Surabaya. The methodology of the research is qualitative research with interpretative-narrativeanalysis based on in depth interview, focus group discussion, and secondary data. The result of this research isthere are two obstacles in implementing Information and Documentation Management Officials by Public Agenciesin Surabaya, which are SOP and Perception challenges.